ANALISIS FAKTOR RISIKO KONDISI LINGKUNGAN LUAR RUMAH DENGAN KASUS MALARIA PADA MASYARAKAT DI INDONESIA - META ANALYSIS 2016-2021 - Ganish Eka Fadillah; R. Azizah (Dian Nuswantoro Semarang, 2022)
Malaria is an infectious disease caused by the Plasmodium which is transmitted to humans through the bite of an Anopheles sp mosquito (WHO, 2020). This study aims to analyze the risk factors for environmental conditions outside the home with malaria cases in the community in Indonesia by systematically tracing research from national publications. This type of research is a systematic review and meta-analysis using JASP software version 0.9.2. The data source used is secondary data for the last 5 years (2016-2021) obtained through the Google Scholar, Science Direct, Pubmed according to the inclusion and exclusion criteria. Obtained 24 research articles relevant to the case control design. Based on the results of the meta-analysis, it was found that the presence of breeding places with an OR of 4.263 (95% CI 2.80 – 6.42), the presence of bushes with an OR of 5.989 (95% CI 1.92 – 18.54), and the presence of cattle pens with OR 2.858 (95% CI 1.04 – 7.85). The conclusion of this study is that the highest risk factor in this study is the variable presence of bushes which has a 5,989 times greater risk of malaria cases in people in Indonesia.